Effects of topography and climate on Neotropical mountain forests structure in the semiarid region. Issue 1 (30th September 2020) - Diogo, Ivan Jeferson Sampaio; dos Santos, Karin; da Costa, Itayguara Ribeiro; dos Santos, Flavio Antonio Maës
Abstract: Question: We aimed to analyze how the topography, temperature and rainfall influence the floristic distribution in three different topographic areas and their surrounding vegetation. We addressed three main questions: (i) How is the distribution of species among the topographic areas? (ii) Which abiotic variable is driving this distribution? and (iii) What is the difference among the mountain forests and between mountain forests and the Caatinga vegetation? Location: The Maranguape mountain forest were divided into three topographic categories: windward (600–800 m, WMA), leeward (600–800 m, LMA) and top (above 800 m, TMA). We also considered another six areas of mountain forests and four Caatinga areas in Ceará State. Methods: We calculated different structural parameters and the floristic diversity of each category. A Principal Correspondence Analysis was performed to analyze the indirect ordination of forest sites by species abundance. A Canonical Correspondence Analysis was conducted to evaluate which variables were driving species distribution. We used non‐metric multidimensional scaling distance and the average linkage method to investigate the similarity among mountain forests and Caatinga. Results: A total of 1, 536 individuals belonging to 144 tree species distributed in 44 families and 93 genera were recorded. Myrtaceae, Fabaceae and Rubiaceae were the most species‐rich families. Myrcia splendens had the highest importance value followed by Guapira nitida and Mollinedia ovata . The leeward slope showed the highest richness and diversity index, whereas the windward showed the highest density and the top showed the highest basal area. The ordination indicated a greater similarity between TMA and WMA than LMA. Conclusion: Our results suggest that temperature, precipitation and slope angle are the abiotic factors driving species distribution in Maranguape. Those mountains are heavily anthropized and continuously explored, therefore these outcomes will be useful for conservation and restoration purposes in the poorly known semiarid region of Northeast Brazil. Abstract : This study presents a rich set of data and findings for mountain forests surrounded by semiarid areas in the Neotropics. These remnants located in Northeast Brazil had a great importance as refuges during paleoclimate oscillations. The study also provides a better knowledge of flora, climate and topographic effects and the forests relationships in arid regions, which is important for recognizing the value of those forests around the globe.